ANALISIS KETERAMPILAN BERBICARA SISWA KELAS I SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA INDONESIA DI SDN 182/I HUTAN LINDUNG - Febi Fajriah; Dwi Nirmala Putri; Tya Noviyanti; Khoirunnisa; Silvina Noviyanti; Desi Kornia Sari (STKIP Subang, 2026)
Language plays a very important role in life. Someone with good language skills will find it easy to communicate with others. Therefore, speaking skills require a process of diligent learning and practice so that a person can master, understand, and apply them optimally. The purpose of this study is to identify and describe students’ speaking skills in Indonesian language classes at the elementary school level. This study employed a descriptive qualitative method; data were collected through observation, semi-structured interviews, and documentation at SDN 182/I Hutan Lindung. The research subjects were the first-grade teacher at SDN 182/I Hutan Lindung and 14 first-grade students. The data analysis stages were conducted through data collection, data reduction, data presentation, and conclusion. The results of the study on the speaking skills of first-grade students at SDN 182/I Hutan Lindung showed that the students’ interest in learning Indonesian was very high, with 13 students liking the lessons and 1 student disliking them. In terms of speaking fluency, 12 students were in the fluent category and 2 students were not yet fluent. The students’ feelings when speaking in front of the class were dominated by negative or anxious feelings (shy/afraid) in 10 students, while 4 students showed positive feelings (brave/happy). In terms of pronunciation accuracy, 9 students were in the good category,